The Effect Composition of Board and Ownership Structure on Corporate Social Responsibility Disclosure: Evidence From Concentrated Ownership Companies - Garaika, Garaika; Margahana, Helisia (Opción, 2019)
Corporate governance in the concentrated ownership context is becoming an increasingly growing discussion. The one important approach to achiev- ing good of corporate governance for sustainable development is sustainable corporate practices which are a focus on the composition of the board and structure of the ownership. This research investigates empirically the impact of board composition and also ownership structure on the disclosure of Cor- porate Social Responsibility (CSR) at concentrated ownership companies con- text. Sample study used the manufactring listed companies in Indonesia Stock Exchang, and selected with purposive sampling. Data analysed with multiple linear regression method. The findings reveal that the board composition is reallysignificantly effect the CSR disclosure. Meanwhile, the independent of commisioners insignificant on CSR disclosure. The other finding reveals that ownership structure would be influence the level of CSR disclosure on con- centrated ownership context, except existence the institutional ownership that found not influence on CSR disclosure.